Analysis of the Implementation of PSAP No.13 Concerning Presentation of Financial Statements for Regional Public Service Bodies at Cigombong Health Center Bogor - Yuppy Triwidatin; Rizki Hidayatullah (International Journal of Managemen Analytics (IJMA), 2023)
This study aims to analyze the presentation of the financial statements of regional public service agencies (BLUD) at the Cigombong Community Health Center, Bogor Regency based on the implementation of PSAP No.13. Comparative qualitative method is a method used to determine the comparison between PSAP No. 13 and the financial reports of Cigombong Health Center, Bogor Regency. data obtained from the implementation of libraries research and fields studies which includes documentation, observations and interviews. The results of the research c ranfie d that presentation of financial statements of the Cigombong Community the BLUD Health Center in Bogor Regency is not in accordance with PSAP Number 13, however there are some that are appropriate, especially reports of changes in excess budget balances, cash flow reports, reports of changes in capital and notes on financial reports. Meanwhile, those that are not fully in accordance with PSAP Number 13 are budget realization reports, balance sheets and operational reports. it is recommended for Cigombong Health Center, especially in the presentation of financial reports, to continue to consistent in the effort to present reliable and trustworthy financial reports   by   referring   to   PSAP number 13 in accordance with the provisions.